2015
DOI: 10.1093/aobpla/plv098
|View full text |Cite
|
Sign up to set email alerts
|

Facultative apomixis and development of fruit in a deciduous shrub with medicinal and nutritional uses

Abstract: The Himalayan Sea buckthorn, Hippophae rhamnoides (Elaeagnaceae) has multifarious uses and employs diverse pathways to reproduce. The species happens to be a facultative apomict, as some seeds are formed without sexual mode (adventive embryony). The combination of sexual and apomictic mode seems to provide reproductive assurance to the plants amidst a less efficient, wind pollination mode. The study provides cytogenetic evidence of the diploid nature of plants and thus adds a new example to the list of known d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The absence of signatures for inbreeding (low F IS values for most markers) suggested low probability for inbreeding depression, which is in line with outcrossing behavior (wind pollination) and likely supports sufficient seed exchange within populations of sea buckthorn. Long distance dispersal of pollen by wind [2,6,16] and seeds by birds [1] contributes hence obviously to inter-regional gene flow.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of signatures for inbreeding (low F IS values for most markers) suggested low probability for inbreeding depression, which is in line with outcrossing behavior (wind pollination) and likely supports sufficient seed exchange within populations of sea buckthorn. Long distance dispersal of pollen by wind [2,6,16] and seeds by birds [1] contributes hence obviously to inter-regional gene flow.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 99%
“…The EST-SSR markers used in our study were developed by Jian et al [6,7] through searching for microsatellite loci in a de novo transcriptome assembly of over 80 million high-quality short EST reads. The transcripts were randomly selected for the development of microsatellites, and, therefore, the EST-SSRs used in our study also represent a random sample of expressed genes.…”
Section: Genetic Diversity and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The plants were assigned sex (male and female) based on field observations (flowers and fruits) as described in our previous studies (Mangla et al 2013(Mangla et al , 2015Mangla and Tandon 2014). Some plants with sparse fruit set (as compared to female plants) were also observed.…”
Section: Study Site and Materialsmentioning
confidence: 99%
“…Sea buckthorn sequences associated with fatty acid and triacylglycerol biosynthetic pathways were identified in the mature seed transcriptome and a comparison of gene expression and oil accumulation in seeds derived from four different developmental stages of fruit indicated that oil deposition begins very early in fruit development 2 . Recently, sea buckthorn was reported to produce seeds either sexually or occasionally by apomixis, with the latter ensuring reproduction in the absence of pollination 12 . Aside from these reports there is no other information available on sea buckthorn lipid biosynthesis and seed development pathways.…”
Section: Introductionmentioning
confidence: 99%